8x+7=4x+37

Simple and best practice solution for 8x+7=4x+37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+7=4x+37 equation:


Simplifying
8x + 7 = 4x + 37

Reorder the terms:
7 + 8x = 4x + 37

Reorder the terms:
7 + 8x = 37 + 4x

Solving
7 + 8x = 37 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
7 + 8x + -4x = 37 + 4x + -4x

Combine like terms: 8x + -4x = 4x
7 + 4x = 37 + 4x + -4x

Combine like terms: 4x + -4x = 0
7 + 4x = 37 + 0
7 + 4x = 37

Add '-7' to each side of the equation.
7 + -7 + 4x = 37 + -7

Combine like terms: 7 + -7 = 0
0 + 4x = 37 + -7
4x = 37 + -7

Combine like terms: 37 + -7 = 30
4x = 30

Divide each side by '4'.
x = 7.5

Simplifying
x = 7.5

See similar equations:

| 6t+3(2+9t)+7= | | 10+2(10)= | | 3(2x-6)=6(1-x) | | 3x-2+x=10-2x | | 5(x+2)=4(9-2x) | | 3+5(5t+1)+8t= | | 4*a-2*1+11=6*a-13 | | 2(x+4)=3(6-x) | | 9*w-2*w+8=4*w+38 | | 3-6x=7-7x | | 7(x+4)=5(x-3) | | 2*m+6=2*m-1 | | (4m+3)9+6m= | | 6*n+21=4*n+57 | | 2+(6m+3)7= | | 6(x+1)=4(x-2) | | 9+9(5+4m)= | | 7(3x+3)=4(4x-1) | | 4+6(3m+2)= | | q+5=2*q+7 | | 3(4x+2)=2(5x-2) | | 4*x+11=x+2 | | 2(2x+3)=3(x+1) | | 6m+7(7m+9)= | | 3x-3=9-x | | 14*k+16*k+88=163 | | 2r-8+4=5(r+1) | | 23+x=2-2x | | 3(2x-4)=2(x-2) | | 3(1+4m)+5m= | | 5(x-2)=4(x-3) | | 1-x=x-1 |

Equations solver categories